In-Plane Cyclic Response of Separated Masonry Infill Walls Using Polymeric Materials at the Surrounding Steel Frames Interface Using 3D FE Analysis - Alireza Karkabadi; Mohammad Iman Khodakarami (Journal of Rehabilitation in Civil Engineering)
Masonry infill walls are commonly used as partitions and exterior walls in many countries. Generally, the masonry wall is executed without any gap from the frame, which leads to the interaction between the structural frame and the infill wall. Interaction between the structural frame and the masonry infill wall can damage the frame and the infill wall. Therefore, it is necessary to find a solution to improve the performance of masonry infill walls in the structural frame. Isolation of the masonry infill wall from the surrounding frame by polymeric material is the idea of this paper to decrease the damage to the structure and masonry infill. In this essay, Finite element models of steel infill frame and isolated infill frame subjected to In-Plane cyclic loading are developed in ABAQUS. For this purpose, three one-bay, one-story masonry-infilled steel frames with different frame ratios of height to the length (H/B) isolated by different polymeric materials with various thicknesses were investigated. Isolation of masonry infill can reduce the base reaction about 25%. In the Isolated Infill wall, the drift’s amount increases about two times compared with the unseparated infill wall. Therefore, it damages the masonry infills up to moderate drifts, while full interaction is still in place drifts are large. Also, infill walls isolated by a softer polymer, have better performance. In brief, isolation of infill wall using polymeric materials improves the behavior of the infill and frame.